New troglomorphic species of Tomocerus with well-developed postantennal organs (Collembola: Tomoceridae) - Yu, Daoyuan; Li, Youbang (Zootaxa, 2016)
Three new troglobitic species of Tomocerus are described from the southwestern karsts of China. All of them have well developed postantennal organs. Tomocerus dong sp. nov. is similar to Tomocerus postantennalis Yu, Zhang & Deharveng and Tomocerus deharvengi sp. nov., but is different from them mainly in the number of prelabral chaetae and the dorsal body chaetotaxy. T. deharvengi sp. nov. is very similar to T. postantennalis but differs from the latter in the cephalic chaetotaxy, the number of manubrial pseudopores and the number of dental spines. T. cthulhu sp. nov. is peculiar for the multi-furcated vesicles of ventral tube, and is different from the three aforementioned species mainly in the dorsal body chaetotaxy. The position of the new species and the relationships between them are discussed.